2007
DOI: 10.1213/01.ane.0000287675.15225.0b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Morphine Enhancement of Spontaneous Seizure Activity

Abstract: The proseizure effect of morphine is mediated through selective stimulation of mu and kappa opiate receptors but not the activation of the delta receptor system. The observed dose-dependent mechanism of morphine neuroexcitation underscores careful adjustment and individualized opioid dosing in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
1
36
0
1
Order By: Relevance
“…Enkephalin inhibited GABA release from inhibitory interneurons, resulting in increased excitability of hippocampal pyramidal cells and dentate gyrus granule cells. The role of enkephalins as pro-convulsive agents is also consistent with the seizureinducing side-effect of high concentration morphine treatment [134,135]. Prodynorphin-derived peptides primarily acted at presynaptic kappa opioid receptors to inhibit excitatory amino acid release from perforant path and mossy fiber terminals [108,136].…”
Section: Dynorphin and Enkephalinmentioning
confidence: 71%
“…Enkephalin inhibited GABA release from inhibitory interneurons, resulting in increased excitability of hippocampal pyramidal cells and dentate gyrus granule cells. The role of enkephalins as pro-convulsive agents is also consistent with the seizureinducing side-effect of high concentration morphine treatment [134,135]. Prodynorphin-derived peptides primarily acted at presynaptic kappa opioid receptors to inhibit excitatory amino acid release from perforant path and mossy fiber terminals [108,136].…”
Section: Dynorphin and Enkephalinmentioning
confidence: 71%
“…It is not clear if this represents a compensatory mechanism against epilepsy because multiple factors determine the anticonvulsant or proconvulsant role of opioids in the brain. For example, morphine depresses electrographic seizure activity under a low concentration, while enhances seizure activity under high concentrations with an apparent dose-dependent manner [217, 223]. SCN80, a non-peptide DOR agonist, both in low or high dose, produced convulsions in the rat, but had little effects in rhesus monkeys [215, 224, 225].…”
Section: Advances In Research On Opioid Receptor Functionsmentioning
confidence: 99%
“…Pfeiffer et al showed that endogenous opioids including β-endorphin, enkephalins and dynorphins and also opiate receptors have an important role in regulation of several neuroendocrine functions [13]. It has been shown that opioids inhibit luteinizing hormone (LH) and thyrotropin secretion in rats [14]. Opioids control neuroendocrine processes in hypothalamic level through releasing hypothalamic releasing or inhibiting factors [15].…”
Section: Introductionmentioning
confidence: 99%